Electric arc-induced damage on electroless Ag film using ionic liquid as a lubricant under sliding electrical contact. (July 2019) - Wen, Xiaoqin; Yuwen, Feiyan; Ding, Zhiqin; Zhang, Wu; Yao, Ruiqing; Lu, Jinjun
Abstract: For Cu-on-Ag film contact, good boundary lubricating property of LP108 allows sliding with low friction coefficient, burnished worn surface and high load-bearing capacity. Under current-loading condition, mechanical separation and recontact of contacting surface produces electric arc and electric arc-induced damage on Ag film depends on polarity of pin and disk. For positive Cu pin against negative Ag film disk, rainbow-like film and transparent LP108 on Ag film are observed. While, for negative Cu pin against positive Ag film disk, removal of Ag film is observed and this produces dark ionic liquid-Ag suspension. In both cases, electric arc does not degrade LP108. Electric arc and electric arc-induced damage on Ag film can be eliminated by ensuring good contacting surface conformity.